Efeitos econômicos e ecológicos da substituição de uso do solo por plantios de eucalipto - Marcelino, Eduardo Henrique Batista (2024)
This study addresses the economic and ecological impacts of eucalyptus forestry expansion in Goiás, considering environmental fragility as a key indicator. By incorporating commonly used methodologies for fragility analysis, it evaluates the vulnerability of natural environments using soil, geological, relief, and rainfall data. The results revealed that Goiás has approximately 138.9 thousand hectares of eucalyptus plantations, with diversified distribution in terms of environmental fragility. Most areas are in the medium fragility category (28.5%), followed by areas with a high degree of fragility (22.6%). These eucalyptus areas encompass different levels of environmental risk, ranging from low to high risk, with notable classes being very low (18.8%) and very high (16.5%). Economic analysis based on the Value of Agricultural Production (VBP) revealed that annual crops showed a negative impact when compared to other land use classes replaced by eucalyptus. These results provide important insights for the sustainable planning and management of eucalyptus forestry areas in Goiás